Absence of scavenger receptor A promotes dendritic cell-mediated cross-presentation of cell-associated antigen and antitumor immune response - Guo, Chunqing (2011)
Given the primary expression of scavenger receptor A (SRA) or CD204 on antigen presenting cells, we investigate the immune-regulatory activities of SRA/CD204 in the context of cross-presentation of cell-associated antigen and the immunogenicity of dying tumor cells. Immunization with dying prostate cancer cells results in profoundly increased control of subsequently inoculated tumors in SRA/CD204 knockout mice. Using OVA-expressing RM1 prostate tumor line (RM1-OVA), we show for the first time that SRA absence greatly enhances dendritic cells (DCs)-mediated cross-presentation of OVA antigen-derived from dying RM1 cells. While the phagocytic ability of DCs is not significantly impacted by the lack of SRA/CD204, DCs deficient in SRA/CD204 display increased expression of inflammatory cytokines and chemokines, as well as co-stimulatory molecules upon interaction with dying RM1 cells, implicating a suppressive regulation of the functional activation of DCs by SRA/CD204. Further, SRA/CD204 deficient DCs pulsed with dying RM1-OVA cells are more effective than wild-type counterparts in priming antigen-specific T-cell responses, resulting in improved control of RM1 tumor growth in both prophylactic and therapeutic settings. Our findings suggest that the increased immunogenicity of dying tumor cells in SRA/CD204 knockout mice is attributed to the altered functions of DCs in the absence of SRA/CD204, which underscores the important role of SRA/CD204 in host immune homeostasis. Selective downregulation or blockade of this immunoregulatory molecule may lead to enhanced potency of DC-based vaccines capable of breaking immune tolerance against cancer.